Value Chain of Chile Piquin Wild Chili (Capsicum annuum L. var. glabriusculum) from Northeastern Mexico - Villalon-Mendoza, Horacio; Ramirez-Meraz, Moises; Garza-Ocanas, Fortunato; Maiti, Rantikanta (International Journal of Bio-resource and Stress Management, 2023)
In Mexico, chili is one of the most important crops for high involvement in the value of the regional agricultural production, generation of income to producers and jobs in wild chili production areas. In the Northeastern of Mexico this wild chili species is strongly rooted in its typical gastronomy.The present study aims to present a model of the economic activities that promote the generation of the value of the “chile piquin”wild chili of the northeastern Mexico, thereby;on the basis of the local production it can reach the final consumer himself which can be likewise, regional, national or international. This exploratory analysis was carried out to collect information of marketing of chili and update about scientific investigations and make a comparative study of our information available and finally to create a frame of reference for future upgrades of the product chain “chile piquin” wild chili which could serve as a basis for other studies. The tool used for obtaining information with statistical validity (p≤0.05) was the method of interviews and of focal group. A flow diagram is developed of the value chain of the “chile piquin” wild chili in northeastern Mexico, which explains theprocesses and pathways that follows the marketing and the increase in the value added of this important product.It was concluded that prices of wild chili have been increased in accordance with the food prices and the fall in the harvested area and production quantity (supply) in Mexico.